In vitro propagation of Drosera intermedia in a single step - Grevenstuk, Tomás (2013)
A simple and efficient protocol for the micropropagation of Drosera intermedia, using cultures initiated from in vitro produced seedlings, is described. Shoot proliferation was significantly influenced by Murashige and Skoog (MS) macronutrient concentration, showing higher multiplication rates for ¼ MS (the lowest concentration), but was not affected by the addition of 0.1 mg dm-3 kinetin. In all cases a multiplication percentage above 90 % was recorded. High rooting percentages (up to 100 %) were obtained in multiplication phase on ¼ MS medium without growth regulators. In average 15.8 plantlets per initial shoot was produced after 8 weeks of culture. All plantlets were successfully acclimatized to ex vitro conditions, exhibiting normal development.